DIGITAL TRANSFORMATION OF EMPLOYEE SERVICES IN THE SORONG DISTRICT GOVERNMENT OF WEST PAPUA - Frengki Fadan; Karmila Sinen; Jusmin (SOSIOEDUKASI, 2026)
Research on the digital transformation of civil service services in the Local Government of Sorong Regency, Southwest Papua Province. Digital transformation is a strategic effort to improve the efficiency, transparency, and accountability of the governance of state civil apparatus (ASN) through the utilization of information and communication technology. This study employs a qualitative method with observations, literature studies, and interviews to understand the digital transformation process and the factors influencing its success. The results of the study indicate significant progress through the implementation of online personnel information systems such as SIMPEGDA and other supporting applications, which facilitate personnel administration and public services. However, challenges such as uneven internet infrastructure, the need for improved digital literacy among ASNs, and data security still need to be addressed. Recommendations focus on strengthening technology infrastructure and enhancing human resource competencies to support optimal digital staffing services. The improvement of human resource competencies requires regular training and mentoring in staffing for civil servants (ASN) to be able to operate digital applications and systems effectively. The digital transformation of staffing services in Sorong Regency is not only an instrument for improving the performance of apparatus but also an important part of realizing an effective, professional, and competitive regional government in the digital era.